(untitled) (Itinera, 2017)
Inside the skeleton of the whale is a performance of the Odin Teatret created in 1996. His subject is inspired by Before the law, parable contained in the novel The Trial of Franz Kafka. The mise-en-scène and the performers’ acting techniques aim at activating the sympathetic resonance with the spectator through a multi-sensorial stimulation. The audience seats around the stage area in front of an elegantly prepared table with bread, olives and red wine. The spectator is invited to participate to a funerary banquet in which hearing, taste, view and smell are involved. By analyzing fragments of this performance, throughout actors’ testimonies as well as reviewers’ and audience’s reception, this paper overviews the psychophysical and sensory involvement of the spectator and shows the different levels of meaning of this performance.